Choosing Modulation Strategies for 2-Stage Combine LLC- and Direct Converter–Modelling, Simulation, Application - Dobrucky, Branislav; Benova, Mariana; Frivaldsky, Michal; Prazenica, Michal (Communications - Scientific letters of the University of Zilina, 2011)
The paper deals with design of switching and control strategy of 2-stage combine LLC- and matrix converter, supplied from DC voltage source. It also deals with comparison of the four different switching control modes: phase-mode control, sinusoidal PWM mode control, pulsedepletion mode control and packet-mode control. Numerical harmonic analysis for total harmonic distortion is used. Simulation and preliminary results of experimental verification are given in the paper.